Financial Performance Analysis Using Camel: Equity and Liquidity : Case Study of PT Bank Bukopin Tbk Period 2018-2022 - Anwar (PT Maju Malaqbi Makkarana, 2024)
The purpose of this research is to analyze the financial performance of PT. Bank Bukopin, Tbk. 2018 – 2022 using the CAMEL ratio which includes aspects of capital, productive assets, management, profitability and liquidity. Implementation of PT health assessment. Bank Bukopin, Tbk. done by qualify several components of each factor, namely components Capital (Capital), Assets (Assets), Management (management), Earnings (Profitability), Liquidity (liquidity) or abbreviated as CAMEL. CAMEL is a factor that really determines the health of a bank. Aspect These are interrelated and cannot be separated. Results of financial performance assessment with the CAMEL ratio shows that seen from the aspect of capital owned by PT. Bank Bukopin, Tbk. Apparently it was above 8%, so PT. Bank Bukopin, Tbk. Own sufficient capital to cover all risks arising from investment funds in productive assets that support risk. Then look at it from aspect management as measured by Net Profit Margin apparently meets the provisions from Bank Indonesia and apart from that from the aspects of earnings and liquidity achieved by PT. Bank Bukopin, Tbk. in accordance with Bank Indonesia regulations.